eDucAçÃo MAteMátiCA AefeTIvA: nomes e movimentos em avessos - Clareto, Sônia Maria; Miarka, Roger (UNESP - Universidade Estadual Paulista, Pró-Reitoria de PesquisaPrograma de Pós-Graduação em Educação Matemática, 2015)
Abstract How to ask about effective research and practices in mathematics education? How to ask about the effectiveness of mathematics education? Crossed by concerns that arise from the struggle with these issues, this article launches itself in defiance: to think of mathematics education as a double: area and movement. Mathematics Education behaving as an area of knowledge and mathematics education behaving as a launching movement. What happens in between this double? Controversy. An unusual and untimely war, a fight that sews area and movement on one side, inside out, front and back, and movement and area and area and movement… On one side and inside out. A double. A movement that becomes territory. An area that cries out for movement. A controversial sewing, weaving one side and its inside out in a single plot. A controversy with mathematics understood as area, but also with mathematics understood as movement. A dispute, more than that, a controversy in the Greek way: polemikós, the art of war. Multiplicity. How many adjectives does math bear? How much can math tolerate being an adjective and not a noun? This writing explores three scenarios: one operates with mathematics education as a field of knowledge, addressing the creation of this area and its institutionalization processes; the other thinks over the movement of mathematics education; a third sews the previous scenarios weaving them: area and movement and mathematics education and Mathematics Education and first name and common name, and so forth…

Resumo Como perguntar por pesquisas e práticas efetivas em educação matemática? Como perguntar pela efetividade da educação matemática? Atravessado por inquietações que brotam do embate com estas questões, o presente artigo se lança em desafio: pensar a educação matemática em um duplo: área e movimento. Educação Matemática se comportando como uma área do conhecimento e educação matemática se lançando como movimento. O que acontece no entre desse duplo? Polêmica. Uma guerra insólita e intempestiva, um combate que costura área e movimento, em direito e avesso e avesso e direito e movimento e área e área e movimento e… Avesso e direito em costura. Um duplo. Um movimento que se territorializa. Um território que clama por movimento. Uma polêmica costura, tece e enreda direito e avesso em uma única trama. Uma polêmica com a Matemática entendida como área, mas também com a matemática como movimento. Uma disputa, mais que isso, uma polêmica à moda grega: polemikós, a arte da guerra. Multiplicidade. Quanto de adjetivação comporta uma matemática? Quanto suporta uma matemática ao ser adjetivo e não substantivo? Este escrito explora três cenários: um deles opera com a Educação Matemática como área de conhecimento, abordando a constituição da área e seus processos de institucionalização; o outro pensa o movimento da educação matemática; um terceiro costura os cenários anteriores em enredamentos: área e movimento e educação matemática e Educação Matemática e nome próprio e nome comum e e e…
AefFecTIvE MAthEmAtiCS eDucAtIOn: names and moviments in inside outs
Keywords: Controversy; Area and Territory; Movement; Multiplicity; Effect; Affection; Effectiveness; Affectiveness; Warriors of Truth; Lovers of the Unusual Battle; Polêmica; Área e Território; Movimento; Multiplicidade; Efeito; Afeto; Efetivo; Afetivo; Guerreiros da Verdade; Amantes da Insólita Batalha